2019
DOI: 10.1097/sla.0000000000003234
|View full text |Cite|
|
Sign up to set email alerts
|

Updated Alternative Fistula Risk Score (ua-FRS) to Include Minimally Invasive Pancreatoduodenectomy

Abstract: Objective: The aim of the study was to validate and optimize the alternative Fistula Risk Score (a-FRS) for patients undergoing minimally invasive pancreatoduodenectomy (MIPD) in a large pan-European cohort. Background: MIPD may be associated with an increased risk of postoperative pancreatic fistula (POPF). The a-FRS could allow for risk-adjusted comparisons in research and improve preventive strategies for high-risk patients. The a-FRS, however, has n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(116 citation statements)
references
References 43 publications
5
92
0
Order By: Relevance
“…Among the patients without POPF, the hospital stay was signi cantly shorter in all patients undergoing MIPD than in all patients undergoing OPD, highlighting the bene t of MIPD regardless of the speci c PJ method used. The multivariate analysis also revealed that male sex was a signi cant risk factor for POPF, in agreement with studies showing that male sex is a risk factors for POPF not only in OPD but also in MIPD [43,44]. However, the underlying cause requires further investigation.…”
Section: Reinforcement Of Water Tightness Of the Anastomosissupporting
confidence: 88%
“…Among the patients without POPF, the hospital stay was signi cantly shorter in all patients undergoing MIPD than in all patients undergoing OPD, highlighting the bene t of MIPD regardless of the speci c PJ method used. The multivariate analysis also revealed that male sex was a signi cant risk factor for POPF, in agreement with studies showing that male sex is a risk factors for POPF not only in OPD but also in MIPD [43,44]. However, the underlying cause requires further investigation.…”
Section: Reinforcement Of Water Tightness Of the Anastomosissupporting
confidence: 88%
“…Interestingly, various parameters that are important predictors of outcomes in pancreatic surgery (eg, pancreatic duct size, pancreatic gland texture, postpancreatectomy hemorrhage, resection margin) were not registered in 1 or more registries. 12,13 The differences are partly because of the various development strategies of the registries. In 2004, the American College of Surgeons National Surgical Quality Improvement Program for pancreatic surgery was built from the initial Veterans Affairs National Surgical Quality Improvement Program (NSQIP), in which data on major operations were captured with the aim to provide feedback and reduce postoperative morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Soft pancreas, which was associated with development of Grade C POPF in this study, has been widely recognized as a risk factor for CR-POPF in previous studies. [7][8][9][10]16,17 Soft pancreas is susceptible to ischemia and injury and is vulnerable to being torn through during suturing. Additionally, exocrine function is generally preserved in soft pancreas, resulting in increased secretion of pancreatic juice, rich in T A B L E 3 Independent risk factors of Grade C POPF on multivariate analysis for prediction of Grade C POPF proteolytic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Increased BMI has been widely recognized to be associated with CR-POPF. [9][10][11]19,20 This can be attributed to the association between elevated BMI and fatty pancreatic parenchyma, as well as the impact of obesity on wound healing. 19,20 The current cohort included Japanese and Taiwanese and they tend to have less BMI than those of Western nations (BMI ≥ 25.0 kg/ m 2 n = 512 (18.5%), BMI ≥ 30.0 kg/m 2 n = 62 (2.2%)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation